Robust Power System Stabilizer based on Static Output Feedback Approach to Enhance Power System Stability. (February 2019) - Chaubey, Piyush; Lather, J.S.; Yelisetti, Srinivas; Manda, Sandeep; Yadav, Nitish Kumar
Abstract: This contribution shows how power system stabilizer adds supplementary signal along with the regular excitation signals to improve the stability of the power system. In literature, PSS has been designed using almost every technique available in control theory i.e from conventional to robust to intelligent control methods. Conventional PSS based on Lead-Lag compensation network is not that much reliable for different loading conditions, as it gives poor performance when the loading condition changes. On the other hand, robust control designs take care of varied operating conditions using the concept of uncertainty. It is well known that the static output feedback problem if feasible can be solved using a pair of coupled linear matrix inequalities. Also, it is shown in literature that the static output feedback problem can be used for direct lower order control design. Researchers have applied the SOF control techniques for direct design of PID controllers, if one exists. This paper involves extensive study and comparison of design techniques for PSS, implements various existing control methodologies for PSS design.